Penatalaksanaan Perawatan Endodontik Pada Molar Kedua Maksila Yang Memiliki Saluran Mesiobukal Dua - Elline Elline; Diana Puspa Indah (Jurnal Kedokteran Gigi Terpadu, 2019)
Background:  The second mesiobuccal canal in mesiobuccal (MB2) roots in maxillary molars is a common finding in root canal treatments.1 The incidence of  MB2  in maxillary molars is 60.4%. The foremost common reasons for treatment failures in permanent maxillary first molars have been as cribed to failure in identifying extra canals particularly in the mesiobuccal root.2 The method for detection MB2 includes dentin removal under magnification and ultrasonic tips. 1 Knowledge of the morphology of the root canal system is important in planning endodontic therapy, as its success relies on the location of all of the canals that can then be disinfected, shaped, and filled.2This case report is written to bring forward the proper and successful management inendodontic treatment of permanent maxillary first molar withfour canals, in which the mesiobuccal root has two canals.  Case Report: A 33 years old male patient complained of cavity on her right upper back tooth and wanted to be filled. Radiographic examination showed that an incomplete access cavity with mesioocclusal cavity of maxillary second molar, which was restored with temporary filling. Access opening and locating MB2 orifice was performed using an ultrasonic tip and under dental operating microscope. The canals were prepared with WaveOne Gold rotary Ni-Ti file with irrigation using 5.25% sodium hypochlorite, 17% EDTA and 2% chlorhexidine gluconate. Calcium hydroxide was used as an intracanal medicament. The canals were obturated with continuous wave compaction technique. Final restoration was performed using composite restoration. Conclusion: The proper locating and treatment of MB2 canals are essential for the success of endodontic treatment of maxillary second molars.